2014
DOI: 10.1097/id.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mandibular Lingual Foramina Related to Dental Implant Treatment With Computerized Tomography

Abstract: With a large sample group, results represented that lingual foramina could be visualized with dental CT, providing useful data for mandibular implant surgeries. Findings suggest that vascular canals and several anastomoses exist in the anterior mandible extending through premolar and molar regions as well. It is imperative to consider these vessels with the dental CT before and during the mandibular surgery to prevent threatening hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 33 publications
10
30
1
7
Order By: Relevance
“…Kingsmill and Boyde [11] reported a similar finding after the investigation of the mandibular height at the mental foramen. In our study, the MLF-LBM in the area superior to GT was measured in 18.28 ± 3.20 mm in dentate group and in 16.21 ± 2.40 mm in edentulous mandibles, similarly to Yildirim et al [29] and contrariwise to Liang et al [13] and Rosano et al [26] who found the distance to be 10.6 ± 5.5 mm and 12.5 ± 2.1 mm. The LLF were located more inferiorly in the mandible with a mean AC-LLF distance of 24.50 ± 4.45 mm (right-sided LLF) and 23.39 ± 5.76 mm (left-sided LLF) and a mean LLF-GT 13.60 ± 6.74 mm (right-sided LLF) and 12.39 ± 6.80 mm (left-sided LLF).…”
Section: Discussionsupporting
confidence: 85%
“…Kingsmill and Boyde [11] reported a similar finding after the investigation of the mandibular height at the mental foramen. In our study, the MLF-LBM in the area superior to GT was measured in 18.28 ± 3.20 mm in dentate group and in 16.21 ± 2.40 mm in edentulous mandibles, similarly to Yildirim et al [29] and contrariwise to Liang et al [13] and Rosano et al [26] who found the distance to be 10.6 ± 5.5 mm and 12.5 ± 2.1 mm. The LLF were located more inferiorly in the mandible with a mean AC-LLF distance of 24.50 ± 4.45 mm (right-sided LLF) and 23.39 ± 5.76 mm (left-sided LLF) and a mean LLF-GT 13.60 ± 6.74 mm (right-sided LLF) and 12.39 ± 6.80 mm (left-sided LLF).…”
Section: Discussionsupporting
confidence: 85%
“…This finding is in accordance with the findings of Liang et al [7] and Sekerci et al [15] and our results. In the current study, Yildirim et al [17] and He at al. [18] estimated that 75.6% and 78.77% of lingual foramen had diameters ≤1 mm, respectively.…”
Section: Discussionmentioning
confidence: 47%
“…Morphol., 35(1):299-305, 2017. La gran mayoría de las publicaciones muestra una alta prevalencia de estos forámenes en CBCT, siendo entre un 79% a un 100% en las muestras estudiadas (Babiuc et al 2011;Gahleitner et al 2001;Katakami et al;Kawashima et al;Yildirim et al 2014). Afortunadamente, esta importante presencia, no se relaciona de manera directamente proporcional con la incidencia de accidentes graves, como hemorragias que puedan llegar a comprometer la vida aérea.…”
Section: Discussionunclassified